The persistence of violence: Colombian popular culture - Miller, Toby (Rutgers University Press, 2020)
Introduction: The Persistence of Violence -- 1. The Absence and Presence of State Militarism : Violence, Football, Narcos / with Alfredo Sabbagh Fajardo -- 2. Industry Policy and Sex Tourism Meet the Case of the Destroyed Plaque / with Olga Lucia Sorzano and Anamaria Tamayo-Duque -- 3. "I Myself Had to Remain Silent When They Threatened My Children" : Colombian Journalists Meet Prime-Time Narcos / with Marta Milena Barrios and Jesús Arroyave -- 4. Green Passion Afloat: The Magdalena River / with Marta Milena Barrios -- Conclusion -- Acknowledgments -- Notes -- References -- Index -- About the Authors.